The mediating effect of mindfulness on adverse childhood experiences and psychological resilience in Turkish female university students - Elif Sezgin (Frontiers in Psychology)
IntroductionAdverse childhood experiences (ACEs) and childhood traumas are known to have lasting negative effects on psychological wellbeing. These early adverse experiences can significantly impair psychological resilience and the capacity to adapt to adversity. While mindfulness has been consistently associated with higher resilience, its potential buffering or mediating role in the relationship between early traumatic experiences and resilience remains underexplored. Although many studies have examined ACEs, fewer have distinguished between general adverse experiences and more severe childhood traumas. This study aimed to determine whether mindfulness mediates the relationship between ACEs, childhood traumas, and resilience among female university students in Turkey. The mindfulness scale used in the study was designed to assess mindfulness and covers four main dimensions: attention and awareness, non-reactivity, non-judgment, and self-acceptance. The possible mediating effect of mindfulness through these dimensions was analyzed.MethodsData were obtained through self-reporting from 255 female university students enrolled in a vocational school in Bursa, Turkey. The survey collected information on ACEs and childhood traumas (emotional abuse, physical neglect, etc.), mindfulness levels (with a focus on attention and awareness), and resilience. Statistical analyses, including mediation analysis, were performed to assess relationships between these variables.ResultsA negative correlation was found between ACEs, including specific forms such as emotional abuse and physical neglect, and resilience. Among these, physical neglect showed the strongest negative association with mindfulness, particularly in the attention and awareness dimension. Furthermore, this dimension of mindfulness significantly predicted higher levels of psychological resilience. Mediation analysis revealed that mindfulness partially mediated the relationship between ACEs, childhood traumas, and resilience. These findings suggest that individuals with higher mindfulness, especially in attention and awareness, may be better protected against the long-term negative impacts of early adverse experiences and trauma on resilience.DiscussionThe findings highlight that emotional abuse and physical neglect significantly reduce mindfulness levels in female university students, with physical neglect having the most substantial impact on attention and awareness. Since mindfulness, particularly attentional awareness, positively predicts resilience, interventions enhancing mindfulness may help mitigate the long-term effects of ACEs. Future research should explore these relationships in broader populations and longitudinal designs.